2021
DOI: 10.25115/eea.v39i5.5209
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Sustainable Urban Transformation Concepts for Economic Development

Abstract: Nowadays cities face numerous challenges amplified to build necessary urban municipal and community capacity to ensure sustainability transformation to respond to the local and global challenges of climate change, inequality, and access to resources. This research combines the study fields of sustainability, economic development, governance of sustainability transformation, providing the multidisciplinary approach as a systemic-oriented view encompassing the social, technological and ecological aspects of urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In the course of the research study, we concluded that currently one of the topical solutions that would ensure sustainable development of the transportation system is the socalled 3-revolutions or 3-transitions [63]. The three components of the sustainable transition should include the replacement of fuel-powered cars by electric cars; the development and adaptation of automated vehicles (the first two components are based on the necessity of technological innovations); and the move from private ownership towards shared mobility in the transportation system.…”
Section: Role Of Car Sharing In Urban Sustainabilitymentioning
confidence: 98%
“…In the course of the research study, we concluded that currently one of the topical solutions that would ensure sustainable development of the transportation system is the socalled 3-revolutions or 3-transitions [63]. The three components of the sustainable transition should include the replacement of fuel-powered cars by electric cars; the development and adaptation of automated vehicles (the first two components are based on the necessity of technological innovations); and the move from private ownership towards shared mobility in the transportation system.…”
Section: Role Of Car Sharing In Urban Sustainabilitymentioning
confidence: 98%
“…It is obvious that today the monitoring system should serve not only as a basis for making appropriate management decisions, but also to provide citizens with operational information about air quality at a specific point in space at a specific time. The second requirement is perhaps even more important than the first, since most often it is the citizens who initiate the relevant management decisions [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In the metallurgical industry of Ukraine, the output of waste exceeds the output of the target product by 6-7 times (Glushchenko, 2021). Considering the crisis phenomena in the economy of Ukraine, the issues of development of greening projects, including innovative technologies for cleaning the atmosphere, processing of industrial waste are especially relevant (Mikelsone et al, 2021). In this regard, the search for sources of funding for the development and implementation of projects for the greening of industrial regions of Ukraine is relevant, especially in the context of acute budget deficits of emerging communities.…”
Section: Introductionmentioning
confidence: 99%